A The ratio of neutrophils l and the mean platelet volume to platelet count ratio as risk factors for febrile convulsions in Zakho: Neutrophil to Lymphocyte Ratio as Risk Factors for Febrile Seizures - A. Mosa, Sherzad; M. Atrushi, Akrem; Shaker Armishty, Farhad; Sh. Abdulrahman , Mehvan (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objective: The most prevalent cause of convulsions in young children is febrile convulsions. The ratio of neutrophils to lymphocytes (NLR), the mean platelet volume (MPV), and the platelet count are indicators of inflammation. Children with febrile seizures usually have higher NLR and MPV and less platelet count. The aim of the study is to evaluate the importance of NLR, MPV, Platelet count, MPV/Platelet, and RDW in feverish children with febrile convulsions. Methods: A case-control study included 163 children with febrile seizures and 163 controls with fever but no seizures. All participants were sent for a red blood cell count (RBC), a white blood cell count (WBC), a hematocrit (Hct), hemoglobin (Hb), a red blood cell distribution width (RDW), a mean corpuscular volume (MCV), a platelet count (PLT), a mean platelet volume (MPV), a monocyte, a lymphocyte, and a neutrophil count, and their percentages were calculated. The absolute neutrophil count divided by the absolute lymphocyte count yields the neutrophil/lymphocyte ratio (NLR). The Mean Platelet volume to platelet count ratio (MPR) was the result of dividing the MPV by platelet count. Results: The mean ages of cases and controls 22.98 ± 12.43 and 23.05 ±12.60 respectively were not significantly different 55.8% of cases and 45.4% of controls were male. Between cases and controls, WBC count, MPV, neutrophil count, and NLR were significantly higher in cases (P = 0.001, 0.001, 0.033, and 0.001 respectively) while lymphocyte and platelet count were significantly lower in cases. Conclusion: children with febrile seizures had significantly greater NLR ratios, MPVs, and lower platelet counts.